Propiedades físicas de la madera de las especies de Samanea saman (Jacq.) Merr (samán) y Triplaris cumingiana Fisch. & C.a. mey (fernán sánchez) térmicamente modificada - Barrera Rosado , Sammy Melissa (2024)
The thermal treatment applied to wood offers advantages such as improving its dimensional stability and resistance against fungi and decay. However, this process can reduce some physical properties. The main objective of the research is to determine the effect of temperatures on the physical properties of S. saman (Jacq.) Merr. (samán) and T. cumingiana Fisch. & C.A. Mey. (Fernán Sánchez) wood. Its purpose is to prevent attacks from microorganisms and improve dimensional stability. Thermal treatment was investigated in T. cumingiana and S. saman specimens at three temperatures (120 ºC, 140 ºC, 160 ºC) and a control group for 6 hours. Variables such as color, wettability, swelling, shrinkage, density, moisture content, and pH value were evaluated. In S. saman, wettability decreased from 120 ºC, and pH showed acidification at 140 ºC (7.09). Samán specimens lightened at higher temperatures. Water absorption and swelling were lower at higher temperatures. In T. cumingiana, wettability increased with temperature, as did pH (7.29 - 7.47). Color did not vary between treatments. Water absorption was lower at 160 ºC, with constant swelling. Density did not change significantly. Shrinkage was lower at 120 ºC and 140 ºC. No significant differences were detected in the coefficient of stability. These results suggest that thermal treatment affects each wood species differently and that certain conditions can improve their properties without compromising stability.